2017
DOI: 10.1039/c7ra02138k
|View full text |Cite
|
Sign up to set email alerts
|

Effects of naturally occurring flavonoids on ferroportin expression in the spleen in iron deficiency anemia in vivo

Abstract: Polyphenols with iron supplement exert variable effects on key players of iron homeostasis in iron deficiency anemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 33 publications
0
10
0
5
Order By: Relevance
“…In addition to demonstrating the pro-apoptotic action exerted by quercetin, quercetagetin and patuletin inside tumor cells, we were also able to determine that these compounds show a selective effect on non-tumor cells, since when normal lymphocytes were treated with the doses applied to the cancer cell lines, the necrotic effect measured was not statistically-significant. Finally, and contrary to their effect on tumor cells, the compounds evaluated herein exhibited a non-antiproliferative effect inside non-tumor cells, relevant data that could be used in other investigations [ 38 ] with flavonoids [ 39 ]. All these results allow us to propose these flavonoids and modifications in substitution patterns in C6 as options that have selective activity against cancer cells but do not damage normal cells, indicating that they may have future utilization in cancer treatment or other biological activities.…”
Section: Discussionmentioning
confidence: 88%
“…In addition to demonstrating the pro-apoptotic action exerted by quercetin, quercetagetin and patuletin inside tumor cells, we were also able to determine that these compounds show a selective effect on non-tumor cells, since when normal lymphocytes were treated with the doses applied to the cancer cell lines, the necrotic effect measured was not statistically-significant. Finally, and contrary to their effect on tumor cells, the compounds evaluated herein exhibited a non-antiproliferative effect inside non-tumor cells, relevant data that could be used in other investigations [ 38 ] with flavonoids [ 39 ]. All these results allow us to propose these flavonoids and modifications in substitution patterns in C6 as options that have selective activity against cancer cells but do not damage normal cells, indicating that they may have future utilization in cancer treatment or other biological activities.…”
Section: Discussionmentioning
confidence: 88%
“…Lesjak et al [66] reported that quercetin treatment can influence intestinal iron uptake by inhibition of iron absorption and by decreasing the expression of duodenal DMT1 and FPN. However, Mazhar et al [67] showed that various polyphenols regulate ferroportin expression and iron homeostasis differently, which might result from differences in their structures. Furthermore, it is required to elucidate the precise mechanism of action of herbal bioactive compounds on mineral absorption in order to improve the efficient utilization of trace elements from various sources (organic/inorganic) in ruminants with a gastrointestinal infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, quercetin can also repress the expression of ferroportin and hephaestin, and subsequently inhibits basolateral iron absorption [23,24]. Another possible mechanism is that quercetin may be able to chelate iron in the enterocytes and the quercetin iron complex being retained in the cytosol [25]. Therefore, the reduction in ferritin level may be as the result of functional cellular iron deficiency [26].…”
Section: Discussionmentioning
confidence: 99%